Applying Early Warning Score (EWS) in hospitals for adult mortality risk factors - Wahyudi, Purnomo; viky, Viky Noviani Hemu; Suprayogi; Setiyarini, Sri (JHeS (Journal of Health Studies), 2023)
The mortality rate among adult hospital patients is a significant indicator in assessing the quality of care and health services. High mortality rates can affect a hospital's reputation, reduce the credibility of medical personnel, and trigger public anxiety. Failure to recognize the worsening of a patient's condition can delay appropriate life support management. This scoping review aims to identify and analyze the Early Warning Score (EWS) application for adults with risk factors for death in regional general hospitals (RSUD). The scoping review was conducted by searching literature using electronic databases from January 2018-May 2023, such as PubMed, ScienceDirect, LibMed UGM, and hand searching. Relevant articles were selected based on inclusion criteria. The results contained two main themes: factors related to mortality in adult patients and the benefits of implementing EWS on the clinical outcomes of adult patients. Implementing EWS in adult patients with high-risk factors for mortality at Regional General Hospitals can help identify the worsening of the patient's condition early, reducing the risk of death. Increasing awareness of the importance of EWS, EWS training, and consistent use of EWS according to hospital protocols can help reduce mortality and improve overall patient clinical outcomes.